A Comparative Analysis of Passenger Demand for Two Airport Hubs in the United States - Selcuk Ertekin; Fassil Fanta (Journal of Applied Marketing Theory)
This paper studies the passenger demand for two airport hubs in the United States using econometric time-series modeling. By focusing on the traditional determinants of demand (national income and price), this paper compares the econometric dynamics of passenger demand for a large and a small airport hub. We found that there is a sustained relationship between income, price, and revenue passenger miles over time. We also found that a shock in GDP causes a disruption that has a lasting impact on passenger demand.